KYTHERA FORTY YEARS ON: THE POTTERY FROM HISTORICAL KASTRI REVISITED1. (22nd August 2014) - Johnston, Alan; Slane, Kathleen; Vroom, Joanita
<x content-type="archive" xml:space="preserve">Abstract</x> We present a review of the post Bronze Age material excavated by Coldstream and Huxley at Kastri on Kythera, as part of the ongoing Kythera Island Project. In particular we refer to material not published in Coldstream and Huxley 1972. Greek material is largely confined to one deposit and dates to the period c.500 to 380 bc. From the Roman period material is more plentiful; the two relevant strata are third and late sixth to seventh centuries, with some earlier Julio-Claudian pieces. While later Medieval pottery also is largely from one deposit, the entirety of it is presented, and a mis en scène with respect to Kytheran modern history is offered.